PENERAPAN PUTUSAN PTUN TERHADAP PEMBERHENTIAN PERANGKAT DESA DITINJAU DARI UNDANG-UNDANG NOMOR 6 TAHUN 2014 - Agustin, Shelia Ristiana; Warka, Made (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
State administrative courts are the courts that have the ability to hear cases that have the authority or competence, such as relative competence and absolute competence. These courts have the jurisdiction to hear matters that have the authority or competence. The ability of a court to hear a matter in accordance with the scope of its jurisdiction is referred to as its "relative competence." Absolute competence refers to the capacity of a court to render a verdict in a case on the basis of the object, material, or subject at issue in the litigation. In this way, the village will be one of the components of governance, which is just one of many facets of governance. The leader of the village is an important position in the administration of the community. A leader is someone who, in addition to carrying out his responsibilities as a leader, also supports and serves the community by carrying out the responsibilities that come with being the head of a village. This indicates that the leader of the city is obligated to steer the regional apparatus in a manner that is consistent with the mandate he was given. Because of its strong ties to the local community, the position of the village apparatus has emerged as one of the most important political issues of the day, and the response of the government has been met with a wide range of opinions and reactions. The village apparatus provides assistance to the village head so that he can fulfill his obligations and responsibilities to the community. If a village leader is found to have violated both government regulations and already established restrictions, then it is possible for him to be removed from his position as head of the community. Village officials who are fired by the village head without the approval of the village head should be protected by legislation. A dismissal of village officials that is carried out in a manner that is not in conformity with applicable laws and regulations may have legal implications in the form of social sanctions for officials who should not get it. This is because there is a lack of openness surrounding this subject